The Influence of Training, Work Motivation and Work Discipline on the Employee Performance of the Public Works and Spatial Planning of the Dharmasraya Regency - ., Adi Chandra; Heryanto (Archives of Business Research, 2019)
This Research Aims To Reveal: (1) the effect of training, partially on employee performance, (2) the effect of partial work motivation on employee performance (3) the influence of work discipline partially on employee performance (4) the effect of training, work motivation and discipline work simultaneously on employee performance. The population of this study were all employees at the Public Works and Spatial Planning Service of Dharmasraya Regency, amounting to 58 people. The sample was taken by all populations, namely 58 people. The analysis method uses multiple regression analysis and is processed with the help of the SPSS version 20.0 program. The results obtained: Partially Training, Work Motivation and Work Discipline have a positive and significant effect on the Employees’ Performance of the Public Works and Spatial Planning of Dharmasraya Regency. Simultaneously Training, Work Motivation and Work Discipline had a positive and significant effect on the Employee Performance of the Public Works and Spatial Planning Department of Dharmasraya with an Adjusted R Square value of 0.469 or 46.9%. Of the three independent variables the most dominant influence on employee performance is training with regression coefficient 0.397. Finally the author suggested to the head of the Dharmasraya District Public Works and Spatial Planning Office to focus more attention on the training given to employees without ignoring the variables of work motivation and work discipline.